Vietnam reduced additional 1.5MtCO2-eq/year through outscaling low-emission technologies in rice production with IRRI-CCAFS' contributions and increases Agriculture-Nationally Determined Contributions mitigation target by 16MtCO2-eq by 2030. - CGIAR Research Program on Climate Change, Agriculture and Food Security (2020)
In its updated Nationally Determined Contributions, Vietnam raised the Agriculture-greenhouse gas mitigation target by 16MtCO2-eq; 100% of Ag-unconditional target will come from rice. With IRRI-CCAFS contributions, climate-smart rice production was introduced to 17,000 extension staff and 75,800 farmers within Vietnam's extension programs; while the Vietnam-Sustainable Agriculture Transformation project almost doubled the low-emission technology adoption area, reaching 163,418ha. Alternate Wetting and Drying and rice straw removal are outscaled in An Giang province. These expansions together saves additional 1.5MtCO20eq/year compared to 2019.